Assessing the Economic Factors Affecting the Growth of Small and Medium Enterprises in Uganda: The Case Study of Selected SMEs in Mukono Municipality - Gordon Ssebudde (Uganda Christian University, 2023)
This study examines the economic factors affecting the growth of Small and Medium Enterprises (SMEs) in Uganda. SMEs play a crucial role in driving economic development, job creation, and poverty reduction in the country. To gain a comprehensive understanding of the factors influencing SME growth, this research examines the impact of access to finance, market dynamics, and human capital development on the growth of SMEs. The research involved collecting data from a diverse sample of SMEs in Uganda, encompassing various sectors, ownership structures, and sizes. The analysis of this data provides valuable insights into the specific challenges and opportunities facing SMEs in Uganda's unique business environment. The study's findings challenge the conventional belief that access to finance is the primary determinant of SME growth. While financial resources are important, other contextual factors, including accessibility to financial institutions, borrowing costs, and the suitability of financial products, may moderate their impact. Consequently, SMEs are encouraged to adopt a more holistic approach to growth, encompassing market responsiveness and human capital development. Market dynamics emerged as a critical factor significantly influencing SME growth. Enterprises that adeptly adapt to changes in customer preferences, anticipate market shifts, and make necessary adjustments experience higher growth rates. Furthermore, the competitive landscape significantly influences pricing decisions, emphasizing the importance of market awareness and responsiveness. Contrary to expectations, human capital development did not exhibit a statistically significant effect on SME growth in Uganda. This suggests that SMEs should critically assess their human resource strategies to ensure alignment with their growth objectives. Optimizing human resource practices to unlock the full potential of employees may be more critical than merely having a skilled workforce. In conclusion, SMEs in Uganda have the potential to drive economic growth, but addressing disparities in access to financial resources, enhancing adaptability to market dynamics, and optimizing human capital development is crucial. Policymakers, business support organizations, and SME owners should collaborate to create an enabling environment that fosters SME growth. Targeted financial interventions, market information dissemination, and investments in education and skills development are recommended to nurture SME growth and contribute to Uganda's economic development. This study provides valuable insights for future research and informs policies and strategies aimed at supporting the resilience and growth of SMEs in Uganda.
This is a dissertation.